Methodology to determine the resistance of sheep to infestation by ticks and infection by piroplasms under field conditions in Tunisia - CGIAR Research Program on Livestock (2020)
The research conducted was the first ever study in Tunisia to identify the low susceptibility of Queue Fine de l’Ouest (QFO) ewes to infestation by ticks and to infection by piroplasms. The QFO breed could therefore be considered for inclusion in breeding programs in high-risk areas of tick occurrence.